KEPUTUSAN WANITA MUSLIM MILENIAL BERWIRAUSAHA: PENGARUH KONSEP DIRI DAN LINGKUNGAN - Kharis Fadlullah Hana (Institut Agama Islam Negeri Padangsidimpuan, 2020)
Technological progress in the 4.0 era was followed by an increase in the Indonesian economy in the field of entrepreneurship. This makes a lot of new business opportunities that are dominated by women. Moreover, there are suggestions from scholars that Muslim women must be able to meet their own needs so that they are not regarded as weak creatures that depend on men. Based on that, the purpose of this study was to determine the effect of self-concept and the environment on their interests and influence on millennial Muslim women's entrepreneurial decisions. This research uses a quantitative method with a post positivism approach. This research analysis technique uses the Structural Equation Model with WarpPLS 6.0 application. The concept of self and environment as exogenous variables, entrepreneurial interests and decisions as endogenous variables. Data were taken using a purposive random sample technique of 210 people. The data population is millennial Muslim women in the Pati Residency area. The results obtained that the variable self-concept has an influence on interest and entrepreneurial decisions of 0.211 with a probability 0.001 and a standard error of 0.047. Environmental variables affect the interest and entrepreneurial decisions of 0.131 with a probability of 0.003 and a standard error of 0.048. This means that the self-concept variable has a greater influence than the millennial Muslim women's environment.